Epidemiology and risk factors of non-esophageal eosinophilic gastrointestinal diseases in Japan: A population-based study - Akinari Sawada; Takumi Imai; Yasutaka Ihara; Fumio Tanaka; Yasuhiro Fujiwara (Allergology International)
Background: Non-esophageal eosinophilic gastrointestinal diseases (non-EoE EGIDs) are allergic conditions where Th-2-predominant inflammation causes symptoms related to gastrointestinal tract dysfunction. No studies have reported the incidence of non-EoE EGIDs. In addition, little is known about the influence of lifestyle factors on the condition. Methods: We used a large health claim database from January 2005 to September 2022. Non-EoE EGIDs cases were identified on the basis of the International Classification of Diseases-tenth Revision code, K52.8. The incidence and prevalence of non-EoE EGIDs were estimated by Poisson and binomial distribution, respectively. For each case, 10 controls were randomly selected for a nested case–control study to identify potential risk factors of non-EoE EGIDs. Results: Of 15,200,895 individuals, 1,368 new cases of non-EoE EGIDs were identified. The incidence and prevalence of non-EoE EGIDs in 2022 were 3.07 (95% CI 2.67–3.52) per 100,000 person-years and 17.23 (95% CI 16.38–18.11) per 100,000 individuals, respectively, which were approximately 6 and 9 times higher than those in 2010. Allergic rhinitis (OR 1.63 (95% CI 1.16–2.29), p = 0.005), chronic sinusitis (OR 2.41 (95% CI 1.58–3.66), p < 0.001), and urticaria (OR 2.32 (95% CI 1.45–3.70), p < 0.001) were related to an increased risk of adult non-EoE EGIDs. Whilst atopic dermatitis (OR 2.28 (95% CI 1.35–3.86), p = 0.006) and the perinatal factors (OR 3.68 (95% CI 1.13–12.02), p = 0.031) were associated with an increased risk of pediatric non-EoE EGIDs. No association was seen with lifestyle factors such as obesity, smoking and alcohol consumption. Conclusions: The incidence and prevalence of non-EoE EGIDs have increased over the past two decades.